Adnexal torsion: clinical, radiological and pathological characteristics in a tertiary care centre in Southern India - Mohan, Swapna; Thomas, Mariam; Raman, Jayasree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adnexal torsion accounts for 2.7% of gynecological emergencies. Early diagnosis can help prevent irreversible damage to ovary. Objective of this study was to analyze the clinical, radiological and pathological characteristics of surgically proven cases of ovarian torsion. Methods: Observational study was carried out from January 2006 to June 2014. Medical records of 38 cases of adnexal torsion were selected and analyzed retrospectively for age, parity, risk factors, clinical presentation, presence of leukocytosis, gray scale ultrasound and colour Doppler features, management, pathological results and post-operative outcome. Results: Adnexal torsion occurred most commonly in reproductive age group (mean 27.89 years) of whom 3 were pregnant. 42% had known risk factors commonly prior pelvic surgery (52.63%) and prior tubal ligation (31.58%). Symptoms include sudden abdominal or pelvic pain (94.74%), vomiting (60.53%) and fever (21.05%). Gray scale USG showed mixed echogenic mass (36.84%), homogenously echogenic cyst (34.21%) anechoic cyst (26.32%) and free fluid (23.68%). Doppler showed absent arterial and venous flow in 52.63%. Cases were managed by detorsion & cystectomy (42.11%), unilateral salpingooophorectomy (47.37%), bilateral salpingooophorectomy (5.26%) and TAH with BSO (5.26%). Histopathology revealed benign serous epithelial tumors (31.58%), mucinous tumors (21.05%), mature teratoma (10.53%), corpus luteal cyst (5.26%), follicular cyst (2.63%) paraovarian cyst (13.16%), endometriotic cyst (2.63%) and ovarian hemangioma (2.63%). Conclusions: High index of suspicion &prompt surgical intervention is necessary to preserve ovarian function even if Doppler shows vascularity. Though detorsion and cystectomy is the choice, salpingooophorectomy may be needed in infracted ovaries and older women. Higher incidence of serous & mucinous tumors in our study suggests reappraisal of ovary sparing surgery for all patients as advocated by few.